Analisis Pengaruh Return On Equity Dan Earning Per Share Terhadap Harga Saham Pt Bank Syariah Indonesia Tbk - Qodhari, Dafelia; Musthofa, M. Wakhid (Jurnal Ekonomika dan Bisnis Islam, 2023)
This research examines the relationship between financial ratios and stock prices in PT Bank Syariah Indonesia. This is a quantitative research study that utilizes E-views version 10 software for data analysis. The data is collected in the form of time series from the annual reports of Bank Syariah Indonesia for the years 2021-2022. The analysis method employed is multiple linear regression. Prior to data analysis, classical assumption tests are conducted to ensure that the model meets the Ordinary Least Squares (OLS) assumptions. The results of the hypothesis testing indicate a significant negative influence of both Retrun on Equity (ROE) and Earning Per Share (EPS) on the stock prices of PT Bank Syariah Indonesia Tbk. The implications of the results of this study will contribute to an investor's decision making for a better investment